PENGEMBANGAN WEBSITE INFORMASI SAWIT PEDIA DAN PERSEPSI PENGGUNA TERHADAP DESAIN DAN KEMUDAHAN PENGGUNAANNYA - Muhammad Reza Harahap; F ' Restuhadi; D ' Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Website is media to meet the information needs for palm subjects. Sawit Pedia Website development based on research purpose that analyze characteristics of users, analyze level of user satisfaction and analyze level of expectations and performance attributes of website. Sampling method using a convenience sampling through online questionnaires Google Forms. Amount of samples is set to 150 people. Characteristics users of Sawit Pedia Website, male 60%, age between 18-28 years old 86%, unmarried 87%, high school graduate/equal 73%, student profession 71%, no income 62%, looking for information motive 69%, internet experience more than 5 years 81%, self-taught learning internet 59%, smartphone uses 49%, internet access at home 55%, internet consumption over 25 hours a week 29% and non-agricultural background 77%. Customer Satisfaction Index (CSI) showed 74.055% are satisfied. Importance Peformance Analysis showed no attribute in Quadrant I. Quadrant II there are twelve attributes that the accuracy of information, ease understanding of information, information actuality, information credibility, ease of use website, search facility, comments column, homepage, header, menubar, banner and widget post recently that must be maintained performance. Quadrant III there are two attributes that intentions and persuasion indicate website does not provide interest content for users. Quadrant IV there are five attributes speed of access, social media, template, calendar widgets and flag counter widget indicates users are not expecting these attributes although high performance and should be eliminated. Sawit Pedia Website development should include a website application Android and iOS that meet the trend of smartphone usage.Keywords : Sawit Pedia Website, Customer Satisfaction Index, User Perception, Importance Performance Analysis, Website Design